2016
DOI: 10.1111/cpr.12268
|View full text |Cite
|
Sign up to set email alerts
|

The PARP family: insights into functional aspects of poly (ADP‐ribose) polymerase‐1 in cell growth and survival

Abstract: PARP family members can be found spread across all domains and continue to be essential molecules from lower to higher eukaryotes. Poly (ADP-ribose) polymerase 1 (PARP-1), newly termed ADP-ribosyltransferase D-type 1 (ARTD1), is a ubiquitously expressed ADP-ribosyltransferase (ART) enzyme involved in key cellular processes such as DNA repair and cell death. This review assesses current developments in PARP-1 biology and activation signals for PARP-1, other than conventional DNA damage activation. Moreover, man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 187 publications
(194 reference statements)
1
81
0
Order By: Relevance
“…Apigenin inhibited Bcl‐xL in both cell lines suggesting the possible involvement of cytochrome C and caspase‐9 activation in apigenin‐induced GBM apoptosis . PARP cleavage results in a loss of the DNA repair function . We showed marked increase in PARP cleavage at 40 and 80 μ m indicating a loss of DNA repair and G2/M cell cycle arrest.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Apigenin inhibited Bcl‐xL in both cell lines suggesting the possible involvement of cytochrome C and caspase‐9 activation in apigenin‐induced GBM apoptosis . PARP cleavage results in a loss of the DNA repair function . We showed marked increase in PARP cleavage at 40 and 80 μ m indicating a loss of DNA repair and G2/M cell cycle arrest.…”
Section: Discussionmentioning
confidence: 68%
“…[32] PARP cleavage results in a loss of the DNA repair function. [33] We showed marked increase in PARP cleavage at 40 and 80 lM indicating a loss of DNA repair and G2/M cell cycle arrest. We observed a G2/M phase cell cycle arrest with flow cytometry confirming the effect of apigenin on PARP inactivation.…”
Section: Discussionmentioning
confidence: 76%
“…Poly‐ADP‐ribose polymerase (PARP) is a nuclear enzyme that signals DNA damage and contributes to the maintenance of genomic integrity . After single‐ and double‐stranded DNA breaks, the catalytic domains of PARP are immediately activated to regulate DNA damage repair through the base excision repair pathway, Elevated levels of PARP in cancer cells compared with normal cells are recognized as one of the mechanisms by which tumor cells avoid apoptosis caused by DNA‐damaging agents .…”
mentioning
confidence: 99%
“…8 In light of a strong rationale that veliparib can be developed as a monotherapy, a clinical study was conducted to evaluate the safety, tolerability, and PK of single-agent veliparib in patients with either BRCA 1/2-mutated cancer or PARP-sensitive tumors. The objectives of this analysis were (1) to characterize the population PK of veliparib and M8 and to assess the potential impact of intrinsic factors on the PK parameters, and (2) to explore the exposure-response relationship for PAR in PBMCs.…”
mentioning
confidence: 99%
“…Also, thick interrupted streams and smaller aggregates as seen in ADPRT1A KO cells (Figure A) were supported by the study that showed PDSA − cells to have unusually thick and transient streams at high cell densities [Garcia et al., ] and altered REGA levels [Wessels et al., ]. PARP‐1 has also been reported to be involved in regulating cellular differentiation [Pavri et al., ; Jubin et al., ]. The Dictyostelium developmental cycle exhibits cell differentiation into prespore and prestalk cells [Jeremyn et al., ].…”
Section: Discussionmentioning
confidence: 72%